Alive : The true story of a triumph of the human spirit - Marshall, Frank; Paramount Pictures; Touchstone Pictures (United States Paramount Pictures, 2002)
A dramatization of the true story of a Uruguayan rugby team whose plane crashes in the Andes Mountains, forcing the survivors to endure extreme conditions and make difficult choices in order to stay alive until rescue.
Based on the true story of the 1972 Andes plane crash survivors.
Rated PG-13.
Keywords: Airplane crash survival; Survival